Estrus synchronization of suckled beef cows by using GnRH, prostaglandin F2α (PGF), and progesterone (CIDR): a multi-location study - J.E. Larson; G.C. Lamb; Jeffrey S. Stevenson; T.W. Marston; Sandra K. Johnson; M.L. Day; T.W. Geary; D.J. Kesler; J.M. DeJarnette; F.N. Schrick (Kansas Agricultural Experiment Station Research Reports, 2004)
Our objectives were to determine whether a fixed-time artificial insemination (TAI) protocol could yield pregnancy rates similar to a protocol requiring detection of estrus and whether inclusion of a CIDR (a vaginal insert containing progesterone) in protocols using gonadotropin-releasing hormone (GnRH) and prostaglandin F2α(PGF) would enhance fertility. Postpartum suckled beef cows (n = 2,630) from 14 locations were assigned randomly to each of five estrus-synchronization protocols using PGF with GnRH and(or) a CIDR. Protocols were Control, CO-Synch, COSynch+ CIDR, Hybrid-Synch, and Hybrid-Synch+CIDR. The percentage of cows cycling at the initiation of estrus synchronization was 66.8%, the percentage of cycling cows ranging from 38 to 90% among locations. Overall pregnancy among locations ranged from 39% to 67%. Pregnancy rates were greatest for the Hybrid-Synch+CIDR (57.9%) treatment, although not significantly different from the CO-Synch+CIDR (53.6%) and Hybrid-Synch (53.0%) treatments, but greater than the Control (52.3%) and CO-Synch (43.4%), which yielded the poorest pregnancy rates. Overall, the Hybrid-Synch+CIDR protocol (AI after detected estrus for 3 days, and then a clean-up TAI) achieved the greatest pregnancy rates, but CO-Synch+CIDR is a reliable, fixed-time AI protocol that gives producers the option to eliminate
Keywords: Cattlemen& #x27; s Day; 2004; Kansas Agricultural Experiment Station contribution; no. 04-242-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 923; Beef; Estrus synchronization; Prostaglandin F2α (PGF); Progesterone (CIDR)